Biofunctional coating of stainless steel surfaces with carvacrol- and eugenol-derived film using atmospheric dielectric barrier discharge plasma: aiming for suppression of biofilm formation and corrosion protection - Getnet, Tsegaye Gashaw [UNESP] (2022)
Metallic biomaterials are the most used materials as orthopedic and dental implants due to their excellent mechanical properties. However, attention must be paid when choosing the materials to be used in the implant medical device to assure their best performance in the biological environment. In addition to good biocompatibility and chemical stability, in several situations, the ideal material must also be able to inhibit implant bacterial colonization. In this context, we have investigated a biofunctional coating of the carvacrol-derived film (CDF) and eugenol-derived film (EDF) on stainless steel surfaces using atmospheric pressure plasma discharge to improve their electrochemical and biological properties. Atomic force microscopy results showed that both CDF and EDF coatings disappeared all the irregularities of the pristine substrate and acquired a uniform surface, free of defects and scratches. Infrared spectra results showed the deposited films largely maintained the mimicking group of the monomer, such as hydroxyl and aromatic, which is a key feature of the film for the antibacterial and electrochemical activity. CDF exhibited a reduction in biofilm growth rate up to 44% for Pseudomonas aeruginosa and 60% for Candida albicans. Similarly, EDF exhibited up to 36% suppression for P. aeruginosa and 52% for C. albicans. These film coatings also decrease the corrosion current density and corrosion rate up to 35% in comparison with the uncoated substrate in 3.5% (w/v) NaCl. Therefore, surface treatment with the present methods is a promising alternative for steel substrate since it improves the electrochemical behavior and suppression tendencies against these microbial biofilms.